Moore receives lst state award (Raton Range Raton, New Mexico, 1987)
Article on Rancher Mary Moore who received the first Pioneer Award given by the Commission on the Status of Women and the New Mexico extension Homemakers Council.
Master list item #: 17
File location is in the Raton File Cabinet
Keywords: Moore, Mary; Commision on the Status of Women; New Mexico Extiension Homemakers Council; New Mexico State Fair; Miners' Hospital; Colfax County Fair Board; National Palomino horse Association Board; Associated county Women of the World; Local History; Biography; Award; Rancher; State Fair; Clubs; Recognistion; Board member; Raton, New Mexico; Albuquerque, New Mexico